Penyesalan (Remorse) pada Remaja Putri yang Telah Melakukan Seks Pranikah - Ria Astiwi; Asniar Khumas; Dian Novita Siswanti (CV. Ulil Albab Corp, 2023)
Premarital sexual behavior among teenagers is currently increasingly prevalent. Various impacts are experienced by teenagers who have had premarital sex such as regret, disappointment, dropping out of school, depression, guilt, and even the desire to commit suicide. The purpose of this study is to find out the remorse of young women who have had premarital sex. This research is qualitative research using phenomenological methods. The analysis technique in data collection used purposive sampling and in-depth interviews. The results of the interviews were written in verbatim form and then through the coding stages, namely open coding, axial coding and selective coding. The results showed that RI and NR respondents had premarital sex during high school while SR was still in junior high school. Respondents now regret having had premarital sex and experience negative feelings, demeaning and self-punishing. The respondent has admitted his mistake and realized the opportunity was wasted. Respondents are now trying to get closer to Allah Subhanahu Wa Ta'ala and are devoted to their parents. Respondents hope to become a better person than before and promise not to do it again. The regret experienced by the respondent does not include regret but remorse.